Development of Timor Local Lurik Peanut Through Breeding with Multigamma Irradiation Method to Obtain Superior Generations - Pasangka, Bartholomeus; Pasangka, Irvandi Gorby; Refli, Refli (Journal of Material Science and Radiation, 2025)
This research focuses on development of local Timor lurik peanut through breeding using multigamma irradiation method, careful selection, and purification to obtain superior generation. The advantage of method is that superior generations are obtained in a relatively short time. Development using modern technology needs to be carried out considering that the production of lurik peanuts at the farmer level has only reached 0.7 t ha-1 to 1.2 t ha-1. The objective of the research is to develop local Timor lurik peanut through breeding using multigamma irradiation method, careful selection, and purification to obtain superior generation seeds. The main research methods are observation, irradiation, careful selection, purification, analysis, and interpretation. Brief procedure of the research: observation for selection of local lurik peanut seeds and identifying the chemical and physical characteristics of parent as comparative materials, preparing the land, cultivating the land, irradiating the seeds, planting on the prepared land, weeding to be free of weeds and fertilizing, irrigating as needed, spraying insecticides as needed, observing and measuring during growth, harvesting, and sorting superior generation seeds. The results obtained: development of local Timor lurrik peanuts through breeding with multigamma irradiation and careful selection obtained superior selected generations that adapt to drought conditions, tolerant of pests and diseases, and high production. The production range of the superior generation resulting from multigamma irradiation was (4.56-4.75) t ha-1 with an average production of 4.63 t ha-1. The percentage increase in production of the superior selected generation was 41.04%, an average water content was 11.2%.